Peritoneal carcinomatosis with intraperitoneal immunotherapy: current treatment options and perspectives. (2nd September 2022) - Wei, Gui-Xia; Du, Yang; Zhou, Yu-Wen; Li, Lin-Juan; Qiu, Meng
ABSTRACT: Introduction: Peritoneal carcinomatosis (PC) is an advanced malignancy that is not sensitive to systemic conventional chemotherapy. Treatment options for PC are usually palliative rather than curative. Cytoreductive surgery and hyperthermic intraperitoneal (IP) chemotherapy are associated with limited efficacy in patients with PC. However, the peritoneum can produce effective immunity by inducing T-lymphocyte recruitment and proliferation, and the unique immune environment of the peritoneum provides the rationale for IP immunotherapy in PC. Areas covered: The authors retrieved relevant documents of IP immunotherapy for PC from PubMed and Medline. This review elaborates on the knowledge of the peritoneal immune microenvironment and IP immunotherapy for PC covering immune stimulators, radioimmunotherapy, catumaxomab, cancer vaccines, chimeric antigen receptor (CAR)-T cells, and immune checkpoint inhibitors. Expert opinion: The prognosis of PC is poor. However, the peritoneal cavity is a unique immune compartment with abundant immune cells which can produce effective immunity. IP immunotherapy may be a promising strategy in patients with PC.